2015
DOI: 10.15537/smj.2015.7.11609
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of methicillin-resistant Staphylococcus aureus nasal colonization among medical students in Jeddah, Saudi Arabia

Abstract: Objectives:To identify Methicillin-resistant Staphylococcus aureus (MRSA) nasal carriage status among medical students during their clinical rotations.Methods:This cross-sectional study detected the prevalence of MRSA among medical students at King Abdulaziz University (KAU), Jeddah, Saudi Arabia, using molecular approaches. Nasal swabs were collected from 150 internship and sixth-year medical students between September 2014 and January 2015, and compared with the control group of 32 third-year medical student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
42
8
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 26 publications
8
42
8
2
Order By: Relevance
“…Various studies have reported S.aureus nasal carriage in medical students ranging from 10%-39%. 3,6,[10][11][12][13] The colonisation rate of MRSA in the present study was found to be 12.66% amongst the medical students. The nasal carriage rate of MRSA in international studies in students ranged from 0% -6.7%.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Various studies have reported S.aureus nasal carriage in medical students ranging from 10%-39%. 3,6,[10][11][12][13] The colonisation rate of MRSA in the present study was found to be 12.66% amongst the medical students. The nasal carriage rate of MRSA in international studies in students ranged from 0% -6.7%.…”
Section: Discussionmentioning
confidence: 80%
“…In Saudi Arabia, the MRSA nasal carriage rate among healthcare workers was reported as 76%. 3 In Delhi, India, MRSA nasal colonization among healthcare workers was reported to be 37.3%. 4 In South India, the MRSA positivity of 8.5% was reported among health care workers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Visos padermės buvo jautrios oksacilinui/ cefoksitinui, tad tarp tiriamųjų nebuvo MASA nešiotojų. MASA nebuvo nustatyta ir 2007-2008 m. atliktame Vilniaus miesto suaugusiųjų populiacijoje tyrime [22] bei kitų autorių atliktų tyrimų metu [16,17,19,28,29]. Ikiklinikinių studijų metu didžiausias šio hospitalinių infekcijų sukėlėjų nešiotojų mastas rastas Indijoje -3,2 proc.…”
Section: Rezultatų Aptarimasunclassified